Integrated ejector cooling, PVT, and MGT system for smart building applications: An exergy and technoeconomic optimization study - Saber Ranjbar Golafshani; Ehsan Houshfar (Case Studies in Thermal Engineering)
Rising global energy consumption has increased pollution and greenhouse gas emissions, underscoring the urgent need for sustainable energy solutions. This research tackles this issue by developing an advanced energy system that combines photovoltaic-thermal, micro-gas-turbine, ejector cooling, auxiliary heater, and hot water storage, all of which operate without relying on batteries. This system allows electricity to be exchanged with the grid, provides heating and cooling, and reduces dependence on traditional energy sources. The study uses energy, exergy, and economic analyses, along with an optimization process to maximize efficiency and reduce costs. Notably, the optimized system achieves a maximum annual exergy efficiency of 19.2 % and a minimum product cost of $17.71/MWh. In contrast, operational analysis shows an exergy efficiency of 11.31 % with a total product cost of $25.78/MWh. These findings highlight the system's ability to improve energy efficiency and reduce costs. The novelty of this work is in developing a new system that uniquely combines solar energy with waste heat recovery—an approach not previously explored. This setup reduces greenhouse gas emissions and provides a practical, battery-free energy management solution for industrial applications. It offers a more sustainable and cost-effective alternative to past models, showing strong potential to support cleaner industrial energy practices.